Strengthening the Role of Community in Improving the Quality of The Manpower - Sulistiyono, Tri; Herlambang, Pratama Herry; Khoirunisa, Dwi Pangestu; Sabri, Ahmad Zaharuddin Sani Ahmad (Universitas Negeri Semarang, 2022)
The quality of labor resources in a country is an important part of development. A qualified workforce will encourage the acceleration of development in an effective, efficient, and competitive manner. In addition, a qualified workforce will also encourage massive economic growth. However, in improving the quality of the workforce, there are still many challenges, one of which is related to the distribution of skills and competencies of workforce certification. This study aims to analyze strategies and patterns of improving the quality of the workforce through community and community strengthening. This study is part of a community service program in the Gunungpati area, Semarang City, Indonesia. Such an approach is expected to support the validity of the devotion results as a helpful output. Observation will be carried out using field studies about the subject matter studied. This devotion uses socialization, games, and motivational training as an effective strategy to instill awareness in the target audience of the dangers and threats to tax blindness as well as the importance of public awareness of the importance of tax payments, not only for themselves but for the state, to ensure the fulfillment of the rights of the community, mainly traders and entrepreneurs as fellow citizens will be increasingly guaranteed and accountable.